USING REDW (READ, EXAMINE, DECIDE, WRITE) STRATEGY TO IMPROVE READING SKILL IN RECOUNT TEXT OF THE EIGHTH GRADERS OF SMP NEGERI 1 TEMANGGUNG IN THE SCHOOL YEAR 2017/2018 - Winanti Enggar Muktisari (Faculty of Education and Teachers Training, 2018)
Reading is an important skill for students that should be mastered in English learning. However, the students of SMP Negeri 1 Temanggung in the school year 2017/2018 find difficulties in learning reading, especially reading the recount texts. The average score of the reading test which was only 55. This score does not reach the standard minimum of the learning target which is 70.The objectives of this research are to describe whether the use REDW strategy can improve the students’ learning motivation in recount text reading skill and to describe how great the improvement of the students’ recount text reading skill of the eighth graders of SMP Negeri 1 Temanggung in the school year 2017/2018.The researcher conducted a classroom action research which was divided into Pre-Cycle, Cycle I, and Cycle II. To collect the data, the researcher used test and non-test technique. The data were analysed using qualitative and quantitative data analysis technique. The researcher took VIII F of SMP Negeri 1 Temanggung as the subject of the research because it has the lowest average score of the reading test. There were 32 students.Based on the result, there is a positive change of the students motivation to learn English. The students participation also increases when the researcher uses REDW strategy and they are enthusiastic to improve their skill in reading a recount text. The result of the test shows the average score of the students who get 70 or higher increased 17.35 points, after they were taught using this strategy. In Pre-cycle, the students average score of reading test is 61.40. Moreover, they have been taught using this strategy, in Cycle I the score is 69.84. The average in Cycle II is 78.75. Based on the above description, the researcher concludes that there is a great improvement from Pre-cycle to Cycle II of the students’ learning motivation and their recount text reading skill.